Criminal Responsibility for Perpetrators of Dating Violence - Wahyu Kurniadi (Dinasti Publisher, 2025)
Dating violence is a form of violence that occurs in non-marital romantic relationships, which often escapes the attention of the law and society. This act of violence can be physical, psychological, sexual, or economic violence committed by a partner against their partner. Even though it is not in a marriage, dating violence still has serious impacts on the victim, both physically and mentally. This article aims to examine how criminal responsibility is imposed on perpetrators of dating violence based on the Indonesian criminal law system. In addition, this article also explores the obstacles to law enforcement against acts of dating violence and the importance of legal protection for victims. Through a normative approach with an analysis of laws and regulations, jurisprudence, and doctrine, this article seeks to provide a comprehensive understanding of the urgency of recognizing dating violence as a serious crime and the need for comprehensive legal protection for victims.